2022
DOI: 10.3390/ijerph192114605
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Embodied CO2 Emissions: Analysis from a Global Input–Output Perspective

Abstract: Global trade drives the world’s economic development, while a large amount of embodied carbon is transferred among different countries and regions. Based on a multi-regional input–output model, the trade embodied carbon transfers of bilateral trade between 185 countries/regions around the world were calculated. On the basis, regional trade embodied carbon transfer patterns and major national trade patterns in six continents, eight major economic cooperation organizations, and six representative countries/regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(30 reference statements)
0
2
0
1
Order By: Relevance
“…The body of literature that analysed this phenomenon focused largely on its dynamics and not its responsiveness to environmental policy, thereby creating an additional layer of vacuum that needs to be taken into consideration when analysing this crucial link. For instance, Zhou et al (2022) provide an interesting insight into this area using a multi-regional input-output model to study embodied carbon transfers between 185 countries and regions. The research found significant regional differences in embodied carbon flows, similar to the findings of Yoon et al (2020), who found China to be a net exporter of embodied carbon emissions to Japan and Korea.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The body of literature that analysed this phenomenon focused largely on its dynamics and not its responsiveness to environmental policy, thereby creating an additional layer of vacuum that needs to be taken into consideration when analysing this crucial link. For instance, Zhou et al (2022) provide an interesting insight into this area using a multi-regional input-output model to study embodied carbon transfers between 185 countries and regions. The research found significant regional differences in embodied carbon flows, similar to the findings of Yoon et al (2020), who found China to be a net exporter of embodied carbon emissions to Japan and Korea.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In similar contexts, studies such as Kang (2021) and Rahman et al (2022) have explored the connection between CO 2 emissions and economic growth, with Kang finding a bidirectional causality between the two. Similarly, studies by Huang and Matsumoto (2022) and Zhou et al (2022) have shed light on the regional differences in embodied carbon flows in domestic imports and exports. Yoon et al (2020) also contribute to the growing body of literature in this area, providing insights into the role of country-level variations in embodied carbon flows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…10 Sin embargo, la falta de herramientas e información a un alto nivel de detalle ha dificultado el análisis de este tipo de problemas para identificar cuáles son los mecanismos llevados a cabo por los países para disminuir sus emisiones. Al respecto, en la literatura sobre el tema se habla de un fenómeno conocido como procesos guiados por la hipótesis de paraísos de contaminación(HPC) [Kornerup et al, 2008;Zhou y Kojima, 2010]; este fenómeno se refiere al traslado de ciertos procesos de producción muy contaminantes de empresas que se encuentran en países desarrollados o económicamente preponderantes en países en vías de desarrollo con políticas ambientales menos estrictas.…”
Section: Análisis Ambiental Desde Una Perspectiva De Insumo-producto:...unclassified